2019
DOI: 10.1039/c8fo01699b
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of phloretin against dextran sulfate sodium-induced ulcerative colitis in mice

Abstract: Oral administration of phloretin, mainly found in apples and strawberries, ameliorates ulcerative colitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 41 publications
6
66
0
Order By: Relevance
“…Similar to a previously study, we noticed that the DSS treatment caused mucosal barrier losses as well as inflammation in the intestinal epithelial cells, resulting in diarrhea and shortened colons in the mice [23]. Flavonoids, including galangin have good anti-inflammatory activity, and some specific flavonoids, such as pinocembrin [16], naringenin [24], and phloretin [25] have been demonstrated to have good anti-colitis effects. However, other flavonoids, such as luteolin, can aggravate DSS-induced experimental colitis, suggesting that the mechanisms of action associated with flavonoids are quite complex [26].…”
Section: Discussionsupporting
confidence: 86%
“…Similar to a previously study, we noticed that the DSS treatment caused mucosal barrier losses as well as inflammation in the intestinal epithelial cells, resulting in diarrhea and shortened colons in the mice [23]. Flavonoids, including galangin have good anti-inflammatory activity, and some specific flavonoids, such as pinocembrin [16], naringenin [24], and phloretin [25] have been demonstrated to have good anti-colitis effects. However, other flavonoids, such as luteolin, can aggravate DSS-induced experimental colitis, suggesting that the mechanisms of action associated with flavonoids are quite complex [26].…”
Section: Discussionsupporting
confidence: 86%
“…Excessive inflammation augments oxidative stress, which has been associated with extensive infiltration of immune cells, and activation of NF-ÎșB signaling and ER stress, thereby causing tissue damage and exacerbation of a patient’s condition [ 12 , 32 , 33 ]. As shown in Figure 6 , DSS significantly enhanced the MDA level, but downregulated the enzyme activity of GPx and CAT.…”
Section: Resultsmentioning
confidence: 99%
“…Occludin was involved in regulating 'leak pathway', whose decreased expression and abnormal distribution result in increased permeability of monolayer intestinal epithelial cells (57). ZO-1 is one of the important components of the tight junction, which attaches Claudin and Occludin proteins to the cytoskeletonis, and often used as an indicator of intestinal inbarrier function (58). Our present results showed that AAP1 could significantly increase the level of Claudin-1, Occludin and ZO-1, suggesting that AAP1 could effectively restore intestinal barrier functions.…”
Section: Discussionmentioning
confidence: 99%